Concurrent Improvement Observed in Patient-Reported Burden and Sensor-Collected Medication Use Among Patients Enrolled in a COPD Digital Health Program - Kaye, Leanne; Gondalia, Rahul; Barrett, Meredith A.; Williams, Melissa; Stempel, David A. (Frontiers in Digital Health, 2021)
Background: The COPD assessment test (CAT) is an 8-item questionnaire widely used in clinical practice to assess patient burden of disease. Digital health platforms that leverage electronic medication monitors (EMMs) are used to track time and date of maintenance and short-acting beta-agonist (SABA) inhaler medication use and record patient-reported outcomes. The study examined changes in CAT and SABA inhaler use in COPD to determine whether passively collected SABA and CAT scores changed in a parallel manner. Methods: Patients with self-reported COPD enrolled in a digital health program, which provided EMMs to track SABA and maintenance inhaler use, and a companion smartphone application (“app”) to provide medication feedback and reminders. Patients completing the CAT questionnaire in the app at enrollment and at six months were included in the analysis. Changes in CAT burden category (by the minimally important difference (MID)), and changes in EMM-recorded mean SABA inhaler use per day were quantified at baseline and six months. Results: The analysis included 611 patients. At six months, mean CAT improved by -0.9 (95% CI: -1.4, -0.4; p<0.001) points, and mean SABA use decreased by -0.6 (-0.8, -0.4; p<0.001) puffs/day. Among patients with higher burden (CAT≥21) at enrollment, CAT improved by -2.0 (-2.6, -1.4; p < 0.001) points, and SABA use decreased by -0.8 (-1.1, -0.6; p < 0.001) puffs/day. Conclusion: Significant and parallel improvement in CAT scores and SABA use at six months were noted among patients enrolled in a digital health program, with greater improvement for patients with higher disease burden.